Radiographic Analysis of Pronation in Operated Hallux Valgus: Short Term Follow-Up. Issue 4 (16th October 2019) - Wagner, Emilio; Wagner, Pablo; Keller, Andres; Bernal, Nazira; Lopez, Mario; Caicedo, Nathaly; Etchevers, Gaston; Mococain, Pablo; Zanolli, Diego
Category: Bunion Introduction/Purpose: Hallux Valgus (HV) is a multiplanar deformity with metatarsal varus and pronation. Pronation is a frequently undiagnosed and/or untreated deformity parameter being a recognized postoperative relapse factor. The objective of this research is to estimate the pronation prevalence in HV and evaluate the pronation correction after conventional Hallux Valgus surgery. Methods: 105 patients with operated Hallux Valgus were followed between 2010 and 2016. Mean age and follow up (months) was 53 and 23 respectively. For all patients, pre and postoperative angular measurements (Pronation angle, hallux valgus angle, HVA, and intermetatarsal angle, IMA) and the operative technique used was recorded. For pronation measurements, a 4-stage classification was used by means of 4 metatarsal templates with different degrees of pronation (0, 10, 20, 30 degrees). Surgical techniques used were Chevron, Scarf and Poscow. Results: Regarding pronation angle, 95 out of 105 patients (90%) had some degree of metatarsal pronation (10% had no pronation). The most common pronation value was 20 degrees (60%). No change in metatarsal pronation angle was observed at final follow up with any technique used. Regarding HVA and IMA pre/postoperatively: HVA: 29/11, IMA: 14/8. Chevron, Scarf and Poscow were used in 15, 67 and 23 patients respectively. 66% of cases decreased sesamoid position in one or more stages. Conclusion: Metatarsal pronation is a frequent finding in Hallux Valgus patients (90%). The most common pronation deformity is 20 degrees. It was not corrected with any technique used (Chevron, Scarf, Poscow). This fact is explained probably because these osteotomies are purely translational aiming to correct the metatarsal varus and not the metatarsal pronation.